Re-Conceptualising Gold-Digging as Gender-Neutral in Obinna Udenwe’s Years of Shame (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2026)
This paper interrogates not only the representation of Gold-Digging in Nigeria’s contemporary socio-cultural and economic narrative, but also contends that the depiction of male characters as gold diggers delineates shifting constructions of masculinity. Moreover, it also explores how masculinity is performed, negotiated, and challenged in Obinna Udenwe’s Years of Shame (2025) with a focus on the male characters. The article seeks to re-conceptualise the idea of gold-digging as a gender-neutral phenomenon. Given the inevitability of rising socio-economic challenges, and the changing gender dynamics, the struggle for survival has become a sordid reality that has contested many misconceptions. In Nigeria’s social discourse on women, gold digging has, over the years, become increasingly associated with men. Recently, writers like Udenwe in his work Years of Shame (2025) substantiates that gold digging is not gendered stereotyped. However, in seeking to extend this notion, the novel seeks to expose gold digging as a societal disorder not limited to the female folk but also to the male folk, which the critics of the work have paid little attention to. Hence, relying on the theories of Bourdieu’s capital theory, Butler’s gender performativity, and Homo Economicus through which this article is analysed, the paper concludes that the issue of gold digging transcends the purview of female folk, but also thrives within the sphere of male folk.
Keywords: Gold-digging; masculinity; gender-neutral; Obinna Udenwe; Homo Economicus